On the Role of Fibrocytes and the Extracellular Matrix in the Physiology and Pathophysiology of the Spiral Ligament - Peeleman, Noa; Verdoodt, Dorien; Ponsaerts, Peter; Van Rompaey, Vincent (Frontiers in Neurology, 2020)
The spiral ligament in the cochlea has been suggested to play a significant role in the pathophysiology of different etiologies of strial hearing loss. Spiral ligament fibrocytes (SLFs), the main cell type in the lateral wall, are crucial in maintaining the endocochlear potential and regulating blood flow. SLF dysfunction can therefore cause cochlear dysfunction and thus hearing impairment. Recent studies have highlighted the role of SLFs in the immune response of the cochlea. In contrast to sensory cells in the inner ear, SLFs (more specifically type III fibrocytes) have also demonstrated the ability to regenerate after different types of trauma such as drug toxicity and noise. SLFs are responsible for producing proteins, such as collagen and cochlin, that create an adequate extracellular matrix to thrive in. Any dysfunction of SLFs or structural changes to the extracellular matrix can significantly impact hearing function. However, SLFs may prove useful in restoring hearing by their potential to regenerate cells in the spiral ligament.